Acute Routine Leukocyte and Neutrophil Counts Are Predictive of Poststroke Recovery at 3 and 12 Months Poststroke: An Exploratory Study. (September 2020) - Nguyen, Vinh A.; Crewther, Sheila G.; Howells, David W.; Wijeratne, Tissa; Ma, Henry; Hankey, Graeme J.; Davis, Stephen; Donnan, Geoffrey A.; Carey, Leeanne M.
Background and Aims . White blood cell (WBC) and neutrophil counts (NC) are common markers of inflammation and neurological stroke damage and could be expected to predict poststroke outcomes. Objective . The aim of this study was to explore the prognostic value of early poststroke WBC and NC to predict cognition, mood, and disability outcomes at 3 and 12 months poststroke. Methods . Routine clinical analyses WBC and NC were collected at 3 time points in the first 4 days of hospitalization from 156 acute stroke patients. Correlations using hierarchical or ordinal regressions were explored between acute WBC and NC and functional recovery, depression, and cognition at 3 and 12 months poststroke, after covarying for age and baseline stroke severity. Results . We found significant increases in NC between <12 hours and 24 to 48 hours time points ( P = .05). Hierarchical regressions, covaried for age and baseline stroke severity, found that 24 to 48 hours WBC ( P = .05) and NC ( P = .04) significantly predicted 3-month cognition scores. Similarly, 24 to 48 hours WBC ( P = .05) and NC ( P = .02) predicted cognition scores at 12 months. Increases in WBC and NC were predictive of increased cognition scores at both 3 and 12 months (positive recovery) though there were no significant associations between WBC and NC and disability or depression scores. Conclusions . Routine acute stroke clinical laboratory tests such as WBC and NC taken between 24 and 48 hours poststroke are predictive of cognition poststroke. It is interpreted that higher rapid immunological activation in the acute phase is an indicator for the trajectory of positive stroke recovery.